Answer : 4 times
Here it's given that ,
- The height and base of the butterfly sitting on the stem (red butterfly) is two times greater than the height and base of the butterfly sitting on the flower .
And we need to find out how many times the area of red winged butterfly is greater than that of sitting on the flower (blue butterfly) .
Let us take ,
- base of blue butterfly be b
- height of blue butterfly be h
- Area be A .
Then ,
- base of red butterfly will be 2b .
- height of red butterfly will be 2h .
- Area be A' .
We know that ,
→ area of the triangle = 1/2 × base × height
So that ,
→ A/A' = (1/2 * b * h) ÷ (1/2 *2b *2h)
→ A/A' = bh/4bh
→ A/A' = 1/4
→ A' = 4A
<u>Henceforth</u><u> the</u><u> area</u><u> of</u><u> </u><u>blue</u><u> butterfly</u><u> is</u><u> </u><u>4</u><u> </u><u>times </u><u>greater</u><u> than</u><u> </u><u>that</u><u> of</u><u> </u><u>red </u><u>winged</u><u> butterfly</u><u> </u><u>.</u>
I hope this helps.
Answer:
-4
Step-by-step explanation:
So we are given the expression: | y - x | + y - 1, and we have our values for (x,y): (-3,-6).
So, we can just start plugging things in and simplifying, so:
| -6 + 3 | - 6 - 1 = | -3 | -7
= 3 - 7
= -4
6+z=10x-2
6+z=-20
Z=-20-6
Z=-26
Hope this helps!
Answer:
The correct answer is (-9, 6) on Edge, the first option
Step-by-step explanation:
Given is <span>(x - 4⁸)
</span>Her factors are <span>(x² - 4²)² (x² + 4²)
</span>Let us prove whether her solution is correct or not.
<span>
(x² - 4²)² (x² + 4²)</span>
(x⁴ - 4⁴) (x² + 4²) ; Follow PEMDAS rule as well as exponential multiplication rule which tells that when exponents are multiplied, the exponents will be added.
By using FOIL(First, Outside, Inside, Last) Method, we can prove if Angelina's solution is correct. NOTE: Do not disregard the positive or negative.
(<u>x⁴</u> - 4⁴) (<u>x²</u> + 4²) ; For the First, multiply the first terms. They are underlined.
This gives you a partial answer: x⁶ (Exponential Law of Multiplication is applied)
(<u>x⁴</u> - 4⁴) (x² <u>+ 4²</u>) ; For the Outside, multiply the outside terms. They are underlined. This gives you an additional to the partial answer: x⁶ + 4²x⁴
<span>(x⁴ <u>- 4⁴</u>) (<u>x²</u> + 4²) ; For the Inside, multiply the inside terms. They are underlined. This gives you an additional to the partial answer: </span>x⁶ + 4²x⁴ - 4⁴x²
(x⁴ <u>- 4⁴</u>) (x² <u>+ 4²</u>) ; For the Last, multiply the last terms. They are underlined. This will give you an additional to the final answer: x⁶ + 4²x⁴ - 4⁴x² - 16⁶ = 0
Final Answer in complete sentence:
The result of multiplying the factors is x⁶ + 4²x⁴ - 4⁴x² - 16⁶ = 0 and is too far compared to (x - 4⁸) which is already a factor.